Guru Berdikari Di Era Revolusi Industri 4.0 - Nova Haryono (Eduprof : Islamic Education Journal, 2021)
The industrial revolution 4.0 is marked by four things, namely super computers, artificial intelligence, cyber systems and manufacturing collaboration. These four things require teachers to increase competitiveness as Human Resources who have competence in the field of education. Therefore, the teacher must be able to compensate for the presence of these four things independently. To create independent students, it is also necessary to have an independent spirit from teachers who are ready in the era of the industrial revolution 4.0. Independent teachers are teachers who are professionally involved in keeping up with the times without always having to depend on the help of others but independently and consciously able to learn to strengthen competence as a teacher.The elements of an independent spirit are one of the solutions for a teacher in facing the revolutionary era 4.0. Teachers are at the forefront of realizing education towards a Glorious Indonesia in 2045 ABSTRAK Revolusi industri 4.0 ditandai dengan empat hal, yaitu komputer super, kecerdasan buatan, sistem siber dan kolaborasi manufaktur. Empat hal ini menuntut guru untuk meningkatkan daya saing sebagai Sumber Daya Manusia yang memiliki kompetensi di bidang pendidikan. Maka dari itu, guru harus mampu mengimbangi kehadiran keempat hal tersebut secara berdikari. Untuk menciptakan peserta didik yang berdikari maka diperlukan pula jiwa berdikari pada guru yang siap di era revolusi industri 4.0. Guru yang berdikari adalah guru yang secara profesional turut serta mengikuti perkembangan jaman tanpa harus selalu bergantung pada bantuan orang lain melainkan secara mandiri dan sadar mampu belajar dalam memperkuat kompetensi sebagai guru. Unsur-unsur jiwa berdikari menjadi salah satu solusi seorang guru dalam menghadapi era revolusi 4.0. Guru menjadi garda terdepan dalam mewujudkan pendidikan menuju Indonesia Gemilang tahun 2045.